2010
DOI: 10.1021/nn1007868
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Band Gap in Hydrogenated Bilayer Graphene

Abstract: We have studied the electronic structural characteristics of hydrogenated bilayer graphene under a perpendicular electric bias using first-principles density functional calculations. The bias voltage applied between the two hydrogenated graphene layers allows continuous tuning of the band gap and leads to transition from semiconducting to metallic state. Desorption of hydrogen from one layer in the chair conformation yields a ferromagnetic semiconductor with a tunable band gap. The implications of tailoring th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
145
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(153 citation statements)
references
References 45 publications
8
145
0
Order By: Relevance
“…When interlayer C-C bonds are created between adjacent graphene planes within AB-and AA-aligned pairs of atoms, two-dimensional (2D) nanostructures are formed resembling the atomic structures of bulk cubic and hexagonal diamond, respectively. [23][24][25][26][27]29 In TBG, where the two graphene layers are rotated with respect to each other by twist angles θ between 0° and 60°, the honeycomb lattices of each layer generate a superlattice of domains that are characterized by a specific type of local alignment; these superlattices have the same symmetry with but a larger periodicity than the original honeycomb lattice and are called Moiré patterns. [43][44][45][46] For twist angles over the range from 0° to ~16° (or, equivalently, from ~44° to 60°), these local domains consist of AAand AB-stacked atoms.…”
Section: Atomic Structurementioning
confidence: 99%
See 3 more Smart Citations
“…When interlayer C-C bonds are created between adjacent graphene planes within AB-and AA-aligned pairs of atoms, two-dimensional (2D) nanostructures are formed resembling the atomic structures of bulk cubic and hexagonal diamond, respectively. [23][24][25][26][27]29 In TBG, where the two graphene layers are rotated with respect to each other by twist angles θ between 0° and 60°, the honeycomb lattices of each layer generate a superlattice of domains that are characterized by a specific type of local alignment; these superlattices have the same symmetry with but a larger periodicity than the original honeycomb lattice and are called Moiré patterns. [43][44][45][46] For twist angles over the range from 0° to ~16° (or, equivalently, from ~44° to 60°), these local domains consist of AAand AB-stacked atoms.…”
Section: Atomic Structurementioning
confidence: 99%
“…[20][21][22] In multilayer graphene, another way of introducing sp 3 bonding and altering the electronic band structure is the formation of interlayer bonds, namely, covalent C-C bonds between atoms of adjacent graphene layers. 16 Several theoretical studies have demonstrated that hydrogenation and formation of such interlayer bonds usually opens a band gap in the electronic band structure; [23][24][25][26][27] again, however, depending on the spatial arrangement of these interlayer bonds, certain features of the electronic band structure of the pristine, non-bonded configuration are preserved. 16 In a recent study, 16 we showed that creation of interlayer C-C bonds in TBG with the individual graphene planes rotated with respect to each other by angles around 30° leads to the formation of superlattices of caged structures (fullerenes) that have the same periodicity with that of the Moiré pattern characteristic of the TBG; depending on the size of these local fullerene structures, the Dirac cones are either preserved or lost opening a narrow gap in the band structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…32,33 We therefore next calculate the effects of an external electric field on electronic structures of bi-layer graphene/β-Si 3 N 4 . The electric field is applied in the direction perpendicular to the graphene with the positive direction pointing from graphene to Si 3 N 4 .…”
mentioning
confidence: 99%